In-situ alloying of Cu in 316L stainless steel by PBF-LB: Influence of laser power and rescanning strategy - Rathinavelu Sokkalingam; Mikael Åsberg; Pavel Krakhmalev (Journal of Materials Research and Technology)
Present work focuses on the in-situ 316L/Cu alloy development by using laser beam powder bed fusion (PBF-LB) additive manufacturing. Influence of the most influential processing parameters i.e., the laser power, and the number of scans i.e., single melting (SM), double melting (DM) and triple melting (TM), on the in-situ alloying ability was studied. At the lowest laser power, 175 W, some 316L powder particles were unmelted and the Cu was not mixed properly into the matrix of 316L. Increasing the laser power from 175 W to 235 W, improves the complete melting of all the components in 316L/Cu powder mix and effective alloying of Cu into 316L with improved homogeneity in its distribution after solidification. However, there is minor copper rich banding at the track overlaps in SM sample prepared at 235 W. Employing of rescanning strategy further improves the homogeneity in distribution of copper owing to the clean and high-quality molten pool with better intermixing by strong molten pool convection.